2015
DOI: 10.1002/jmrs.89
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac dose‐sparing benefits of deep inspiration breath‐hold in left breast irradiation: a systematic review

Abstract: IntroductionDespite technical advancements in breast radiation therapy, cardiac structures are still subject to significant levels of irradiation. As the use of adjuvant radiation therapy after breast-conserving surgery continues to improve survival for early breast cancer patients, the associated radiation-induced cardiac toxicities become increasingly relevant. Our primary aim was to evaluate the cardiac-sparing benefits of the deep inspiration breath-hold (DIBH) technique.MethodsAn electronic literature sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 32 publications
8
69
0
2
Order By: Relevance
“…only found four studies, with a total of 69 subjects, that have reported on reproducibility or stability of DIBH treatment 31. Three of the studies used breast surface, and one heart position, to estimate the reproducibility and stability.…”
Section: Discussionmentioning
confidence: 99%
“…only found four studies, with a total of 69 subjects, that have reported on reproducibility or stability of DIBH treatment 31. Three of the studies used breast surface, and one heart position, to estimate the reproducibility and stability.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the so far puplicated planning studies on the use of DIBH and the reduction of cardiac dose, only contain a comparison of 3D and IMRT treatment techniques [1,2,3,4]. Also, only the evaluation of the mean dose exposure is taken into account for late effects and radioinduced heart diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Tangential three-dimensional conformal or intensity modulated radiotherapy planning approaches allow for more homogenous target coverage, and at the same time, dose-volume estimations of delivered dose to organs at risk. Different strategies to reduce the dose to thoracic organs are being researched [108][109][110] . Image-guided deep inspiratory breath hold is a reproducible and stable radiotherapy technique, which can be implemented as a voluntary, non-computer-controlled technique in breast/chest wall and/or locoregional radiotherapy, including its use in low-resource settings 111 .…”
Section: Radiotherapymentioning
confidence: 99%
“…Image-guided deep inspiratory breath hold is a reproducible and stable radiotherapy technique, which can be implemented as a voluntary, non-computer-controlled technique in breast/chest wall and/or locoregional radiotherapy, including its use in low-resource settings 111 . Deep inspiratory breath hold has been shown to significantly reduce dose to heart, left anterior descending coronary artery, and lung 108,112 .…”
Section: Radiotherapymentioning
confidence: 99%